Characterization and finite element modeling of Galfenol minor flux density loops. (January 2015) - Deng, Zhangxian; Dapino, Marcelo J
This paper focuses on the development of a 3D hysteretic Galfenol model which is implemented using the finite element method (FEM) in COMSOL Multiphysics ® . The model describes Galfenol responses and those of passive components including flux return path, coils and surrounding air. A key contribution of this work is that it lifts the limitations of symmetric geometry utilized in the previous literature and demonstrates the implementation of the approach for more complex systems than before. Unlike anhysteretic FEM models, the proposed model can describe minor loops which are essential for both Galfenol sensor and actuator design. A group of stress versus flux density loops for different bias currents is used to verify the accuracy of the model in the quasi-static regime. Through incorporating C code with MATLAB, the computational efficiency is improved by 78% relative to previous work.